A Phase-Dependent Model of Sorghum (Sorghum bicolor) Cold Acclimation: Integrating Multi-Layered Networks and Alternative Splicing Signatures - Kurt, Firat (Mdpi, 2026)
Cold stress limits sorghum productivity, yet the temporal organization of its molecular response remains incompletely understood. In this study, a multi-layered transcriptomic approach was employed to analyze the cold response of sorghum across 6 h, 12 h, and 24 h. By integrating differential expression, weighted gene co-expression network analysis (WGCNA), and alternative splicing (AS) profiling, a phase-dependent regulatory model was proposed. Quantitatively, the network was initially resolved into 17 co-expression modules, which were subsequently consolidated into 10 final modules. A core set of 147 transcription factors (predominantly AP2/ERF and NAC families) was consistently associated with the response across time points. During the early shock phase (6 h), the broad repression of energy-associated transcripts suggests rapid intracellular stabilization. The transition phase (12 h) was characterized by transcriptomic shifts suggestive of chromatin-level regulation and post-transcriptional adjustments. By late acclimation (24 h), the reorganization of stress-associated modules indicates a progression toward a stabilized regulatory state. Furthermore, the identification of dynamic AS events across multiple regulatory families suggests that isoform diversification is a crucial parallel regulatory layer. Moving beyond static expression profiling, this study provides a comprehensive temporal framework of sorghum cold acclimation and identifies phase-specific candidate genes for future experimental validation in C4 crops.
Keywords: Sorghum; Cold Stress; Rna-Seq; Transcription Factors; Regulators; Kinases; Alternative Splicing; Epigenetics